Co-production process optimization and carbon footprint analysis of biohydrogen and biofertilizer from corncob by photo-fermentation. (May 2023) - Zhang, Zhiping; Ai, Fuke; Li, Yameng; Zhu, Shengnan; Wu, Qiyou; Duan, Zhisai; Liu, Hanchuan; Qian, Liyang; Zhang, Quanguo; Zhang, Yang
Graphical abstract: Highlights: Co-production of biohydrogen and biofertilizer is more profitable. The CHY of 120 mesh corncob was the highest (71.16 mL/g TS). The freeze-dried fertilizer had better slow-release effect. Fertilizer of 120 mesh corncob had the best slow-release effect. Abstract: In this study, corncob was taken as substrate, the co-production process of biohydrogen and biofertilizer by photo-fermentation was investigated and its carbon footprint analysis was conducted to evaluate the carbon transfer pathway. Biohydrogen was produced by photo-fermentation, and the hydrogen producing residues were immobilized by sodium alginate. Cumulative hydrogen yield (CHY) and nitrogen release ability (NRA) was taken as references, and the effect of substrate particle size on the co-production process was evaluated. Results showed that due to the porous adsorption properties, corncob size of 120 mesh was the optimal one. Under that condition, the highest CHY and NRA were 71.16 mL/g TS and 68.76%, respectively. The carbon footprint analysis indicted that 7.9% carbon element was released as carbon dioxide, 78.3% carbon element was immobilized in the biofertilizer, and 13.8% carbon element was lost. This work is significant of the biomass utilization and clean energy production.